The Effect of Stroke Length and SPM Variations on Production Rate and Economic Profitability of AH-052 Well - Mohd Wirawan; Novrianti; Aldo Setiawan (BBPMGB LEMIGAS, 2026)
AH-052 well, which uses a Sucker Rod Pump (SRP), began to experience a decline in productivity over time. The performance of the AH-052 oil well in South Sumatra, which uses a Sucker Rod Pump (SRP) as an artificial lift system. This well has a depth of 289.87 meters with a perforation interval of 236.52–238.05 meters. Before optimization, this well showed a production rate of 264 BFPD with a water cut of 97% and a pump efficiency of only 72.28%. Through variations in the SRP pump system parameters, the available equipment specifications were 1 1/4 inch and 1 1/8 inch rods, rod number 109, plunger 2 inch, stroke length (SL) of 140 inch, and pump speed (n) of 5 spm. The parameters used successfully increased pump efficiency significantly to 91.12% and production rate to 381.2 BFPD. Economic feasibility analysis based on the Production Sharing Model Contract Cost Recovery contract model showed very positive results. This project generated a Net Present Value (NPV) of MU202.08, an Internal Rate of Return (IRR) of 1153%, a Pay Out Time (POT) of 0.086 years, and a Profitability Index (PI) of 22.56. Based on these indicators, this optimization project is considered highly financially viable and provides substantial benefits.